New forms of foreign investment in developing countries: Determinant features, characteristics and prospects - Werner Olle (Intereconomics, 1983)
To a growing extent, since the early 1970s “new forms” of foreign investment have developed which constitute a departure from full ownership of the capital by the foreign investor and the practice of “packaged” management services. What view is to be taken of these new forms of investment from the development policy aspect?
Keywords: 330; Direct Investment